Medical issues relating to the Sydney Olympic Games - Milne, C.; Shaw, M.; Steinweg, J. (Sports Medicine, 2000)
The Sydney Olympic Games in 2000 represent a significant medical and sporting challenge. Prior planning is the key to optimal performance, and team medical staff should be familiar with major medical and injury concerns of athletes and officials well prior to departure. A comprehensive team medical kit should be organised. Travel will be over great distances for many teams, so particular attention to optimising sleep and hydration is essential. The Olympic village experience can be overwhelming for some athletes, and medical staff should provide informed advice on food, transport and safety issues. Heat is less likely to be an issue than at recent summer Olympic Games, but should not be ignored completely. Major incidents can occur at any major sporting festival, and team medical staff should be appropriately prepared for these. All team medical staff should be aware of the current list of banned substances, and seek to minimise drug use by their athletes. After the event, an appropriate debriefing session should be held with a view to planning improvements for the future.